2014
DOI: 10.1111/ijn.12240
|View full text |Cite
|
Sign up to set email alerts
|

‘We are nurses, they are doctors’: Barriers to nurses' roles in pain management following surgery in Jordan

Abstract: This study explored barriers to nurses' roles in pain management following surgery in Jordan. A qualitative approach using four focus group discussions (n = 4) was used. The total convenience sample of surgical wards nurses included 25 nurses. The analysis revealed two categories explaining the context and perceived barriers affecting nurses' roles in pain management. First were barriers within bedside nursing, comprising attention-seeking patients, 'buzzer obsession' and family interferences. Second were barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
(54 reference statements)
0
30
1
Order By: Relevance
“…Nurses in this study were reported to be around the parents and children only during routine clinical assessment and for implementing procedures. Although, this finding could be explained by the parents perceived higher social status of doctors over nurses [27]; parents in this study voiced a need for nurses to be more physically present and engage in more communication with both the parents and children. Social-work professionals need to be involved in the care plans of SCD children and their parents according to our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Nurses in this study were reported to be around the parents and children only during routine clinical assessment and for implementing procedures. Although, this finding could be explained by the parents perceived higher social status of doctors over nurses [27]; parents in this study voiced a need for nurses to be more physically present and engage in more communication with both the parents and children. Social-work professionals need to be involved in the care plans of SCD children and their parents according to our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Assessment of pain in a child may be influenced by the parent (118,(125)(126)(127) and the physical and social context (128) in which the assessment takes place. Studies have shown that ward culture impacts pain assessment practices (126,129) and nurses often attribute deficiencies in pain assessment practices to staffing issues and heavy workloads (15,(130)(131)(132).…”
Section: Factors Influencing the Assessment And Management Of Painmentioning
confidence: 99%
“…Although nurses in Poland are professionally independent since 1996, it seems that they are not viewed as partners by many hospital‐based physicians. The problem of ‘power imbalance’ though is not unique to Polish health‐care system (Shoqirat ). We strongly feel that to tackle that problem, more emphasis should be put on close cooperation between nurses and doctors.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%